Approaching integrated urban-rural development in China: The changing institutional roles - Yuheng Li; Zhichao Hu; Yansui Liu (European Regional Science Association (ERSA), 2014)
Ever since the twenty-first century, the Chinese government has been undertaking a series of rural-favored policies and measures to promote comprehensive development in rural China. The fundamental purpose is to accomplish integrated urban-rural development (IURD) given the ever enlarging urban-rural inequalities during the post-reform era. Considering the long time biased policies against the countryside, the paper aims to examine the institutional roles in approaching the IURD. IURD at provincial level in China is assessed by the principal component analysis of selected variables which represent the socioeconomic integration between urban and rural areas. The institutional roles in promoting IURD include three aspects: decentralization in directing local rural development; employment, social security system and material circulation system which influence the free production factor flows between urban and rural areas; education, medical treatment and culture system which influence public services between urban and rural areas. We carry out panel data analysis to investigate the relationship between institutions and IURD at provincial level in China in the period 1980-2010. The analysis also controls variables such as locational factors, population density, per capita GDP in each province. The data mainly refers to Comprehensive Statistical Data and Materials on 60 Years of New China and National Statistical Yearbooks in recent years. Research results show significant and dynamic roles of institution in promoting IURD at different time periods.
Keywords: 330; urban-rural equalized development; urbanization; transformation; institutional roles; China